2016
DOI: 10.1051/0004-6361/201527242
|View full text |Cite
|
Sign up to set email alerts
|

The Nainital-Cape Survey

Abstract: Context. The Nainital-Cape Survey is a dedicated ongoing survey program to search for and study pulsational variability in chemically peculiar (CP) stars to understand their internal structure and evolution. Aims. The main aims of this survey are to find new pulsating Ap and Am stars in the northern and southern hemisphere and to perform asteroseismic studies of these new pulsators. Methods. The survey is conducted using high-speed photometry. The candidate stars were selected on the basis of having Strömgren … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 92 publications
4
61
0
Order By: Relevance
“…where M V and M I denote absolute magnitudes in V and I band, respectively. We note here that no significant metallicity gradient has been seen across the LMC and SMC (e.g., Grocholski et al 2006;Cioni 2009;Parisi et al 2009;Feast et al 2010;Deb & Singh 2014;Joshi et al 2016) hence any variation in the MCs P-L relations due to metallicity variation is not considered in the present study. Even if we accept any variation in the metallicity at all as reported in some previous studies (e.g., Tammann et al 2003;Carrera et al 2008;Kapakos & Hatzidimitriou 2012;Dobbie et al 2014) the difference in reddening is found to be ∼0.001 mag which is insignificant in comparison of the scatter in the P-L diagrams itself.…”
Section: Methodology Of Reddening Determinationmentioning
confidence: 58%
See 4 more Smart Citations
“…where M V and M I denote absolute magnitudes in V and I band, respectively. We note here that no significant metallicity gradient has been seen across the LMC and SMC (e.g., Grocholski et al 2006;Cioni 2009;Parisi et al 2009;Feast et al 2010;Deb & Singh 2014;Joshi et al 2016) hence any variation in the MCs P-L relations due to metallicity variation is not considered in the present study. Even if we accept any variation in the metallicity at all as reported in some previous studies (e.g., Tammann et al 2003;Carrera et al 2008;Kapakos & Hatzidimitriou 2012;Dobbie et al 2014) the difference in reddening is found to be ∼0.001 mag which is insignificant in comparison of the scatter in the P-L diagrams itself.…”
Section: Methodology Of Reddening Determinationmentioning
confidence: 58%
“…For example, Borissova et al (2004Borissova et al ( , 2006 suggested the existence of homogeneous, old and metal-poor stellar halo in the LMC based on the velocity dispersion of RR Lyrae stars. On the basis of spatial and age distributions of Cepheids reported in the Optical Gravitational Lensing Experiment (OGLE) Phase-III survey, Joshi & Joshi (2014) and Joshi et al (2016) affirmed that a major star formation triggered in these two dwarf galaxies at ≈ 200 ± 50 Myr ago. Choi et al (2018) revealed a significant warp in the south west region of LMC outer disk towards SMC and an off-centered tilted LMC bar which they believe is consistent with a direct collision between the two clouds in agreement with the earlier studies (e.g., Besla et al 2012;Carrera et al 2017;Zivick et al 2018Zivick et al , 2019.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations